SplintR ligation-triggered in-situ rolling circle amplification on magnetic bead for accurate detection of circulating microRNAs - Yang, Sha; Yuan, Lijia; Luo, Xing; Xiao, Ting; Sun, Xiaoqing; Feng, Liu; Deng, Jiezhong; Zhan, Mei (PeerJ, 2025)
The circulating microRNAs (miRNAs), endogenous noncoding RNAs, post-transcriptionally participate in multiple processes during cell growth and development. Moreover, dysregulation of miRNAs expression is intricately associated with cancer. Currently, challenges of high homology, sequence similarity, and low abundance encountered in the detection of target miRNAs in complex samples need to be addressed. Biosensors established for miRNAs detection suffer from limitations in terms of sensitivity, specificity and high cost. Herein, a miRNA detection method based on in-situ RCA on magnetic bead catalyzed by SplintR ligase was proposed to achieve high sensitivity and high specificity. The following steps are included: (1) formation of P1-P2-miRNA double-stranded complex under catalyzation of SplintR ligase, and the release of P1-P2 single strand under denaturation; (2) enrichment of P1-P2 single chain by streptavidin-modified magnetic beads (SM-MB); (3) in situ RCA on surface of magnetic beads; (4) fluorescence detection. After optimization of experimental conditions, miRNA-155 detection with improved sensitivity and specificity was achieved. The detection limit was low to 36.39 fM, and one-base mismatch discrimination was demonstrated. Also, the clinical practicability for circulating miRNA-155 detection was preliminarily validated in human serum samples.
Keywords: Circulating microRNAs detection; SplintR; In-situ rolling circle amplification